Electrocardiographic and echocardiographic characteristics in HIV-1 and non-HIV-1 infected children at Muhimbili National Hospital, Dar es Salaam, Tanzania (Tanzania Medical Journal, 2007)
Objective: The objective of the study was to describe the electrocardiographic and echocardiographic characteristics of HIV–1 infected children. aged 18 months to 7years.at Muhimbili National Hospital. Methods: A cross sectional comparative study was carried out between April 2001 and January 2002. All consecutive children aged between 18 months to 7 years admitted in the paediatric wards and those attending the out patient department between April 2001 and January2002 were enrolled for the study. Children who tested HIV-1 positive comprised the study group and those who tested HIV-1 negative formed the comparative group.Results: The study population consisted of 280 children, 160 males and 120 females. The overall prevalence of cardiovascular disorders was (83/280) 29.6%.The prevalence of cardiovascular disorders was significantly higher in HIV infected than non-HIV infected children,(46.2% versus 23.3%, p< 0.0001).The common cardiac disorders strongly associated with HIV infection were pericardial effusion, (26.9%) (p< 0.0002), Left ventricular dysfunction (LVD) 24.7% (p< 0.0004),Dilated cardiomyopathy (DCM) 24.4% (p< 0.0001), and sinus tarchycardia 20.5% (p< 0.0001). Endocarditis was not detected.Conclusion: Cardiac diseases are common in HIV infected children. ECG detectable sinus tachycardia prompts further investigation by Echocardiogram to detect the cardiac abnormalities in HIV-1 infected children. Tanzania Medical Journal Vol. 19 (1) 2004